A method for injection molding low gloss, wear-resistant automobile instrument panel
By using plastic modified agents, light absorbers and modified talcum powder in the injection molding method of the car dashboard, the contradiction between performance improvement and mechanical performance in existing technologies is solved, and low luster, abrasion resistance Increase with mechanical strength.
Patent Information
- Application Number
- CN202410602239.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-05-15
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2044-05-15
AI Technical Summary
The prior art improves the performance of automotive instrument panels by adding additives and additives, making it difficult to achieve the expected effect, and there are differences in compatibility between materials and additives, which may reduce mechanical properties when improving gloss and wear resistance.
The injection molding method of a low-luster, wear-resistant car instrument board is used to use 4-hydroxybenzene borne and 3-cymbal-1,2-propylene glycol to prepare plastic modifiers and perform it with PVC powder and chores. Reflected, then adding light -absorbent and modified talcum powder to squeeze out the melting pouring through a double screw extrusion machine to form an injection molding material with a high degree of high -tech connection.
The low gloss, abrasion resistance and mechanical strength of the automotive dashboard have been realized, and the contradiction between performance improvement and mechanical performance in existing technologies.
Smart Images

Figure SMS_1 
Figure SMS_2 
Figure SMS_3
Abstract
Description
[0001] The invention relates to the technical field of instrument panel injection molding, and in particular to an injection molding method for a low-gloss, wear-resistant automobile instrument panel. Background Art
[0002] As a key component in the vehicle interior, the car dashboard not only carries the task of displaying information for the driver and passengers, but also adds a sense of beauty to the interior space of the car in terms of vision and touch. In order to avoid obvious reflection under strong light, which will cause glare and discomfort to the driver and passengers, the car dashboard must have good visual effects and performance, including low gloss, wear resistance, surface texture, stability and combination with other components, so as to ensure the beauty and practicality of the entire interior space of the car.
[0003] The manufacturing method of the existing automobile dashboard mainly adopts the injection molding technology, which heats and melts the plastic, injects it into the mold at high speed and high pressure, and then smoothly demolds the mold after cooling to obtain the automobile dashboard product. Some studies have reduced the glossiness of the automobile dashboard by adjusting the injection molding parameters such as injection speed, pressure, mold temperature, etc. However, such methods have certain limitations, such as it is difficult to ensure the overall low glossiness and uniform texture of the surface; there are also methods to improve the performance of the material by adding additives and auxiliaries, but the effect of the additives on the performance of the material is difficult to achieve the expected effect, and there are also differences in compatibility between the material and the additive. While improving the glossiness and wear resistance of the material, the mechanical properties of the material may be reduced.
[0004] In view of the technical defects in this aspect, a solution is now proposed. Summary of the invention
[0005] The purpose of the present invention is to provide an injection molding method for a low-gloss, wear-resistant automobile instrument panel, which is used to solve the technical problem that the prior art improves the performance of the automobile instrument panel by adding additives and auxiliaries, but it is difficult to achieve the expected effect, and there are also differences in compatibility between the automobile instrument panel material and the additives. While improving the gloss and wear resistance of the material, the mechanical properties of the material may be reduced. The wear resistance, gloss and mechanical properties of the automobile instrument panel need to be further improved.
[0006] The purpose of the present invention can be achieved through the following technical solutions:
[0007] A method for injection molding a low-gloss, wear-resistant automobile instrument panel comprises the following steps:
[0008] S1. Add 4-hydroxyphenylboric acid and tetrahydrofuran into a three-necked flask and stir until the system is dissolved, add 3-mercapto-1,2-propanediol and a catalyst into the three-necked flask, raise the temperature of the three-necked flask to 45-55° C., keep the temperature for reaction for 8-10 hours, and perform post-treatment to obtain a plastic modifier;
[0009] The synthetic reaction principle of plastic modifier is:
[0010]
[0011] S2, adding PVC powder, nitrile rubber, plastic modifier and additives into a Hake internal mixer, and mixing for 15-20 minutes to obtain a mixed plastic;
[0012] Add the mixed plastic into a two-roll mixer, set the temperature of the front roller to 165-175°C, the temperature of the rear roller to 160-165°C, adjust the distance between the two rollers to 3-5mm, pass through the mixer several times until the rollers are wrapped, and discharge the material to obtain an injection molding precursor;
[0013] S3, adding 2,2-dihydroxymethyl propionate, hydroxypropyl-terminated polydimethylsiloxane, 1,5-pentanediol, xylene and a catalyst into a three-necked flask protected by nitrogen and stirring, raising the temperature of the three-necked flask to a micro-reflux of the system, adding isophorone diisocyanate dropwise into the three-necked flask, and after the addition is complete, heat-retaining the reaction for 90-120 minutes, adding modified silica into the three-necked flask in multiple batches, and after the addition of the modified silica is complete, heat-retaining the reaction for 2-3 hours, and post-treating to obtain a light-absorbing modifier;
[0014] The synthetic reaction principle of the light-absorbing modifier is:
[0015]
[0016]
[0017]
[0018]
[0019]
[0020] S4, adding the injection molding precursor, light absorbing modifier, modified talcum powder and additives into a twin-screw extruder, melt-extruded into a molding die, demolded, and obtaining a car dashboard.
[0021] Furthermore, in step S1, the molar ratio of 4-hydroxyphenylboric acid to 3-mercapto-1,2-propylene glycol is 1:1, the ratio of 4-hydroxyphenylboric acid, tetrahydrofuran and catalyst is 1 g:5 mL:0.1 g, the catalyst is deionized water, and the post-treatment operation comprises: after the reaction is completed, the temperature of the three-necked flask is increased to 70-80° C., and reduced pressure distillation is performed until no liquid flows out to obtain a plastic modifier; in step S2, the weight ratio of PVC powder, nitrile rubber, plastic modifier and additive is 70:30:4:3, the additive is composed of calcium oxide and polyethylene glycol-200 in a weight ratio of 2:1, the temperature of the internal mixer is 160-170° C., and the rotation speed is 35-45 r / min.
[0022] Furthermore, the preparation method of 2,2-dihydroxymethylpropionic acid is as follows: 2,2-dihydroxymethylpropionic acid and cyclohexane are added to a three-necked flask and stirred, the temperature of the three-necked flask is increased to 50-55° C., triethylamine is added dropwise to the three-necked flask, and after the addition is completed, the reaction is kept warm for 30-50 minutes, and 2,2-dihydroxymethylpropionic acid is obtained by post-treatment.
[0023] The synthetic reaction principle of 2,2-dihydroxymethyl propionate is:
[0024]
[0025] Furthermore, the dosage ratio of the 2,2-dihydroxymethylpropionic acid, cyclohexane and triethylamine is 1g:6mL:1g, and the post-treatment operation includes: after the reaction is completed, the temperature of the three-necked flask is reduced to 10-20°C, the mixture is stirred for 10-15min, filtered, the filter cake is rinsed three times with cyclohexane and then dried, the filter cake is transferred to a drying oven at a temperature of 50-60°C, and dried to constant weight to obtain 2,2-dihydroxymethylpropionic acid salt.
[0026] Furthermore, the preparation method of modified silica is: add nano silicon dioxide, anhydrous ethanol, and 3-aminopropyltriethoxysilane into a three-necked flask, ultrasonically disperse for 30-50 minutes, transfer the three-necked flask to an iron stand with a mechanical stirrer, stir, add 8vt% ammonia water into the three-necked flask, increase the temperature of the three-necked flask to 50-60°C, keep warm for reaction for 4-5 hours, and post-treat to obtain modified silica.
[0027] The synthetic reaction principle of modified silica is:
[0028]
[0029] Where: is silicon dioxide;
[0030] Furthermore, the dosage ratio of the nano-silica, anhydrous ethanol, 3-aminopropyltriethoxysilane and 8vt% ammonia water is 5g:40mL:3g:15mL, and the post-treatment operation includes: after the reaction is completed, the temperature of the three-necked flask is lowered to room temperature, filtered, the filter cake is washed with purified water until it is neutral, and the filter cake is transferred to a drying oven at a temperature of 60-70°C, and dried to constant weight to obtain modified silica.
[0031] Further, the preparation method of modified talcum powder is:
[0032] Add isocyanatepropyltriethoxysilane, tetrahydrofuran and ethylene glycol into a three-necked flask protected by nitrogen, stir, and react at room temperature for 2-3 hours to obtain a modified solution for later use;
[0033] Add talcum powder, ethanol and 10vt% ammonia water into a three-necked flask and ultrasonically disperse for 30-50min. Fix the three-necked flask on an iron stand with mechanical stirring and stir. Raise the temperature of the three-necked flask to 50-60℃. Add the modified liquid dropwise into the three-necked flask. After the addition is complete, keep the temperature for reaction for 3-5h and post-treat to obtain modified talcum powder.
[0034] Furthermore, the molar ratio of isocyanatepropyl triethoxysilane and ethylene glycol is 1:1, and the dosage ratio of isocyanatepropyl triethoxysilane, tetrahydrofuran, talcum powder, ethanol and 10vt% ammonia water is 3g:10mL:5g:20mL:10mL, and the post-treatment operation includes: after the reaction is completed, the temperature of the three-necked flask is lowered to room temperature, filtered, the filter cake is washed three times with anhydrous ethanol and then dried, and the filter cake is transferred to a drying oven at a temperature of 60-70°C, and dried to constant weight to obtain modified talcum powder.
[0035] Furthermore, in step S3, the amount ratio of 2,2-dihydroxymethylpropionate, hydroxypropyl-terminated polydimethylsiloxane, 1,5-pentanediol, xylene, catalyst, isophorone diisocyanate and modified silica is 1.5g:1g:1g:12mL:0.05g:4.3g:7g, the catalyst is dibutyltin dilaurate, and the post-treatment operation includes: after the reaction is completed, the temperature of the three-necked flask is increased to 90-100°C, toluene is evaporated under reduced pressure, and the light absorbing modifier is obtained by post-treatment.
[0036] Furthermore, in step S4, the weight ratio of the injection molding precursor, the light absorbing modifier, the modified talcum powder and the additive is 100:23:11:6, and the additive is composed of a dispersant, a plasticizer, an antioxidant, and a lubricant in a weight ratio of 2:2:1:1. The dispersant is one or more of calcium stearate, zinc stearate, magnesium stearate, and cadmium stearate, and the plasticizer is one or more of dioctyl phthalate, diester phthalate, diisodecyl phthalate, and tricresyl phosphate. The antioxidant is one or more of butylated hydroxyanisole, dibutyl hydroxytoluene, and tert-butylhydroquinone, and the lubricant is one or more of oleamide and ethylene bisstearamide; the temperatures of the six temperature intervals of the twin-screw extruder from the feed end to the discharge end are set to 250°C, 255°C, 260°C, 260°C, 260°C, and 260°C, respectively, and the spindle speed of the twin-screw extruder is 18r / min.
[0037] The present invention has the following beneficial effects:
[0038] The low-gloss, wear-resistant automobile dashboard of the present invention is prepared by modifying PVC powder and nitrile rubber by using a plastic modifier, grafting and modifying phenol groups on the molecular chains of the PVC powder and the nitrile rubber, and uniformly mixing a light-absorbing modifier modified with an isocyanate group and modified talcum powder according to a specific dosage ratio, and then melt-casting is performed to form a spatial network cross-linked injection molding material with the light-absorbing modifier as an anchor point, thereby improving the cross-linking degree of the automobile dashboard, reducing the surface gloss of the automobile dashboard, and improving the mechanical strength of the automobile dashboard.
[0039] The plastic modifier of the present invention is prepared by reacting 4-hydroxyphenylboronic acid and 3-mercapto-1,2-propylene glycol under the condition of a catalyst, wherein the dihydroxyl functional group on the 3-mercapto-1,2-propylene glycol can react with the hydroxyl group in the 4-hydroxyphenylboronic acid to form an ether bond, thereby preparing a phenol-modified thiol-containing compound, wherein the thiol group on the plastic modifier can react with the active chlorine in PVC and the unsaturated carbon-carbon double bond on the nitrile rubber, and the plastic modifier is grafted onto the PVC or the nitrile rubber in the form of chemical bonding to obtain an injection molding precursor, wherein when preparing the injection molding precursor, polyethylene glycol-200 is added thereto to promote uniform dispersion of various components, and calcium oxide can neutralize hydrogen chloride generated when the plastic modifier reacts with PVC to generate calcium chloride, thereby preventing degradation of PVC molecular chains in an acidic high-temperature environment; the modified talcum powder of the present invention is prepared by reacting isocyanate triethoxysilane and ethylene glycol in a molar ratio of 1:1. To a modification liquid with hydroxyl-modified triethoxysilane, in an alkaline environment, the siloxane bonds of the modification liquid are broken and react with the active functional groups on the surface of talc to form a polysiloxane coating on the surface of talc. The hydroxyl functional group modified on the surface of talc is a polar functional group with electronegativity, which enables it to interact with the polar functional groups in PVC or nitrile rubber by hydrogen bonds, which helps to enhance the compatibility between filler and resin. The hydroxyl functional group can also exhibit surfactant-like properties, which helps to reduce surface tension and make the modified talc easier to disperse evenly in the mixture of PVC and nitrile rubber. Talc is an opaque filler. Talc particles will increase the texture and irregularity of the surface, increase the surface roughness of the car dashboard, improve the scattering and absorption capacity of the car dashboard to light, and reduce the surface gloss of the material. The hardness of talc is relatively high. After addition, the surface hardness of the car dashboard can be increased, thereby increasing its wear resistance.
[0040] During the preparation of the light absorption modifier of the present invention, nano silicon dioxide is modified by 3-aminopropyltriethoxysilane to obtain modified silicon dioxide with a large amount of amino modifications on the surface; after 2,2-dihydroxymethylpropionic acid and triethylamine undergo an acid-base neutralization reaction to obtain 2,2-dihydroxymethylpropionate, 2,2-dihydroxymethylpropionate, hydroxypropyl-terminated polydimethylsiloxane, 1,5-pentanediol and isophorone diisocyanate are reacted to obtain a polyurethane segment with isocyanate termination; the isocyanate groups on the polyurethane segment react with the amino groups on the modified silicon dioxide to obtain the light absorption modifier; the large amount of isocyanate groups on the light absorption modifier can react with the phenol on the injection molding precursor or the hydroxyl groups on the talc powder, thereby improving the crosslinking of the automobile instrument panel degree; the 2,2-dihydroxymethyl propionate contained in the polyurethane segment can form hydrogen bonds or other non-covalent interactions with the active functional groups in the injection molding precursor, thereby improving the surface hardness of the car dashboard. The polysiloxane segment has good flexibility and forms an anchoring effect in the car dashboard, thereby improving the impact resistance of the car dashboard; silica is used as an inorganic filler. Due to the presence of nanoparticles, the surface is not smooth enough, resulting in an increase in the surface roughness of the material. Light will be scattered more on the surface, thereby reducing the amount of reflected light and causing a decrease in gloss. Nano-silica is also a hard material, so the addition of a light-absorbing modifier can form a hard protective layer on the material surface, which helps to reduce friction and wear, thereby improving wear resistance. DETAILED DESCRIPTION
[0041] The technical solution of the present invention will be clearly and completely described below in conjunction with the embodiments. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Example
[0042] This embodiment provides a method for injection molding a low-gloss, wear-resistant automobile instrument panel, comprising the following steps:
[0043] S1. Preparation of plastic modifier
[0044] Weigh: 13.7 g of 4-hydroxyphenylboric acid and 68.5 mL of tetrahydrofuran are added into a three-necked flask and stirred until the system is dissolved. 10.8 g of 3-mercapto-1,2-propanediol and 1.37 g of deionized water are added into the three-necked flask. The temperature of the three-necked flask is increased to 45°C and kept warm for 8 hours. The temperature of the three-necked flask is increased to 70°C and distilled under reduced pressure until no liquid flows out to obtain a plastic modifier.
[0045] S2. Preparation of injection molding precursor
[0046] Weigh: 700 g of PVC powder, 300 g of nitrile rubber, 40 g of plastic modifier, 20 g of calcium oxide and 10 g of polyethylene glycol-200 and add them into a Haake internal mixer. The temperature of the internal mixer is set to 160° C. and the speed is 35 r / min for 15 min to obtain a mixed plastic.
[0047] Add the mixed plastic into a two-roll mixer, set the temperature of the front roller to 165°C, the temperature of the rear roller to 160°C, adjust the distance between the two rollers to 3mm, pass through the mixer several times until it wraps around the rollers, and discharge the material to obtain an injection molding precursor.
[0048] S3. Preparation of modified silicon dioxide
[0049] Weigh: 50 g of nano-silica, 400 mL of anhydrous ethanol, and 30 g of 3-aminopropyltriethoxysilane, add into a three-necked flask, ultrasonically disperse for 30 min, transfer the three-necked flask to an iron stand with a mechanical stirrer, stir, add 150 mL of 8vt% ammonia water into the three-necked flask, raise the temperature of the three-necked flask to 50°C, keep warm for 4 hours, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral, transfer the filter cake to a drying oven at a temperature of 60°C, and dry to constant weight to obtain modified silica.
[0050] S4. Preparation of light absorbing modifier
[0051] Weigh: 15 g of 2,2-dimethylolpropionic acid and 70 mL of cyclohexane are added to a three-necked flask and stirred. The temperature of the three-necked flask is raised to 50° C., 15 g of triethylamine is added dropwise to the three-necked flask. After the addition is complete, the reaction is kept warm for 30 minutes. The temperature of the three-necked flask is lowered to 10° C., and the mixture is kept warm and stirred for 10 minutes. The filter cake is filtered, and the filter cake is rinsed three times with cyclohexane and then dried. The filter cake is transferred to a drying oven at a temperature of 50° C. and dried to constant weight to obtain 2,2-dimethylolpropionic acid salt;
[0052] Weigh: 30 g of 2,2-dihydroxymethylpropionate, 20 g of hydroxypropyl-terminated polydimethylsiloxane, 20 g of 1,5-pentanediol, 240 mL of xylene and 0.1 g of dibutyltin dilaurate, add them into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to the system micro-reflux, add 86 g of isophorone diisocyanate dropwise into the three-necked flask, after the addition is complete, keep warm and react for 90 min, weigh 140 g of modified silica, divide the modified silica into 5 equal parts, add them into the three-necked flask in batches, with an interval of 3 min between each batch, after the addition of the modified silica is completed, keep warm and react for 2 h, raise the temperature of the three-necked flask to 90°C, evaporate toluene under reduced pressure, and post-treat to obtain a light absorbing modifier.
[0053] S5. Preparation of modified talcum powder
[0054] Weigh: 24.7 g of isocyanatepropyltriethoxysilane, 82.3 mL of tetrahydrofuran and 6.2 g of ethylene glycol, add into a three-necked flask protected by nitrogen, stir, react at room temperature for 2 h, and obtain a modified solution for standby use;
[0055] Weigh: 41.2 g of talcum powder, 164.8 mL of ethanol and 82.4 mL of 10 vt% ammonia water, add into a three-necked flask and ultrasonically disperse for 30 min, fix the three-necked flask on an iron stand with a mechanical stirrer and stir, raise the temperature of the three-necked flask to 50°C, add the modified liquid dropwise into the three-necked flask, keep warm for 3 h, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake three times with anhydrous ethanol and then drain, transfer the filter cake to a drying oven at 60°C, dry to constant weight, and obtain modified talcum powder.
[0056] S6, Automobile dashboard injection molding
[0057] Weigh: 1000g of injection molding precursor, 230g of light absorption modifier, 110g of modified talc, 20g of calcium stearate, 20g of dioctyl phthalate, 10g of butylated hydroxyanisole, and 10g of oleamide and add them into a twin-screw extruder. The temperatures of 6 temperature zones from the feed end to the discharge end of the twin-screw extruder are set to 250°C, 255°C, 260°C, 260°C, 260°C, and 260°C respectively. The main shaft speed of the twin-screw extruder is 18r / min. The product is melt-extruded into a molding mold through the twin-screw extruder and demolded to obtain a car dashboard. Example
[0058] This embodiment provides a method for injection molding a low-gloss, wear-resistant automobile instrument panel, comprising the following steps:
[0059] S1. Preparation of plastic modifier
[0060] Weigh: 13.7 g of 4-hydroxyphenylboric acid and 68.5 mL of tetrahydrofuran are added into a three-necked flask and stirred until the system is dissolved. 10.8 g of 3-mercapto-1,2-propanediol and 1.37 g of deionized water are added into the three-necked flask. The temperature of the three-necked flask is increased to 47°C and kept warm for 9 hours. The temperature of the three-necked flask is increased to 75°C and distilled under reduced pressure until no liquid flows out to obtain a plastic modifier.
[0061] S2. Preparation of injection molding precursor
[0062] Weigh: 700 g of PVC powder, 300 g of nitrile rubber, 40 g of plastic modifier, 20 g of calcium oxide and 10 g of polyethylene glycol-200 and add them into a Haake internal mixer. The temperature of the internal mixer is set to 165° C., the speed is 40 r / min, and the internal mixer is mixed for 17 min to obtain a mixed plastic.
[0063] Add the mixed plastic into a two-roll mixer, set the temperature of the front roller to 170°C, the temperature of the rear roller to 163°C, adjust the distance between the two rollers to 4mm, pass through the mixer several times until it reaches the wrap roller, discharge the material, and obtain an injection molding precursor.
[0064] S3. Preparation of modified silicon dioxide
[0065] Weigh: 50 g of nano-silica, 400 mL of anhydrous ethanol, and 30 g of 3-aminopropyltriethoxysilane, add into a three-necked flask, ultrasonically disperse for 40 min, transfer the three-necked flask to an iron stand with a mechanical stirrer, stir, add 150 mL of 8vt% ammonia water into the three-necked flask, raise the temperature of the three-necked flask to 55°C, keep warm for 4.5 h, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral, transfer the filter cake to a drying oven at a temperature of 65°C, and dry to constant weight to obtain modified silica.
[0066] S4. Preparation of light absorbing modifier
[0067] Weigh: 15 g of 2,2-dimethylolpropionic acid and 70 mL of cyclohexane are added to a three-necked flask and stirred. The temperature of the three-necked flask is raised to 53° C., 15 g of triethylamine is added dropwise to the three-necked flask. After the addition is complete, the reaction is kept warm for 40 minutes. The temperature of the three-necked flask is lowered to 15° C., and the mixture is kept warm and stirred for 13 minutes. The filter cake is filtered, and the filter cake is rinsed three times with cyclohexane and then dried. The filter cake is transferred to a drying oven at a temperature of 55° C. and dried to constant weight to obtain 2,2-dimethylolpropionic acid salt;
[0068] Weigh: 30 g of 2,2-dihydroxymethylpropionate, 20 g of hydroxypropyl-terminated polydimethylsiloxane, 20 g of 1,5-pentanediol, 240 mL of xylene and 0.1 g of dibutyltin dilaurate, add them into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to the system micro-reflux, add 86 g of isophorone diisocyanate dropwise into the three-necked flask, after the addition is complete, keep warm and react for 105 min, weigh 140 g of modified silica, divide the modified silica into 5 equal parts, add them into the three-necked flask in batches, with an interval of 4 min between each batch, after the addition of modified silica is completed, keep warm and react for 2.5 h, raise the temperature of the three-necked flask to 95° C., evaporate toluene under reduced pressure, and post-treat to obtain a light absorbing modifier.
[0069] S5. Preparation of modified talcum powder
[0070] Weigh: 24.7 g of isocyanatepropyltriethoxysilane, 82.3 mL of tetrahydrofuran and 6.2 g of ethylene glycol, add into a three-necked flask protected by nitrogen, stir, react at room temperature for 2.5 h, and obtain a modified solution for standby use;
[0071] Weigh: 41.2 g of talcum powder, 164.8 mL of ethanol and 82.4 mL of 10 vt% ammonia water, add into a three-necked flask and ultrasonically disperse for 40 min, fix the three-necked flask on an iron stand with a mechanical stirrer and stir, raise the temperature of the three-necked flask to 55°C, add the modified liquid dropwise into the three-necked flask, keep warm for 4 hours, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake three times with anhydrous ethanol and then drain, transfer the filter cake to a drying oven at a temperature of 65°C, dry to constant weight, and obtain modified talcum powder.
[0072] S6, Automobile dashboard injection molding
[0073] Weigh: 1000g of injection molding precursor, 230g of light absorption modifier, 110g of modified talc, 20g of zinc stearate, 20g of diester phthalate, 10g of butylated hydroxytoluene, and 10g of ethylene bisstearamide and add them into a twin-screw extruder. The temperatures of 6 temperature zones from the feed end to the discharge end of the twin-screw extruder are set to 250°C, 255°C, 260°C, 260°C, 260°C, and 260°C respectively. The main shaft speed of the twin-screw extruder is 18r / min. The product is melt-extruded into a molding mold through the twin-screw extruder and demolded to obtain a car dashboard. Example
[0074] This embodiment provides a method for injection molding a low-gloss, wear-resistant automobile instrument panel, comprising the following steps:
[0075] S1. Preparation of plastic modifier
[0076] Weigh: 13.7 g of 4-hydroxyphenylboric acid and 68.5 mL of tetrahydrofuran are added into a three-necked flask and stirred until the system is dissolved. 10.8 g of 3-mercapto-1,2-propanediol and 1.37 g of deionized water are added into the three-necked flask. The temperature of the three-necked flask is increased to 55°C and the reaction is kept warm for 10 hours. The temperature of the three-necked flask is increased to 80°C and the plastic modifier is obtained by distillation under reduced pressure until no liquid flows out.
[0077] S2. Preparation of injection molding precursor
[0078] Weigh: 700 g of PVC powder, 300 g of nitrile rubber, 40 g of plastic modifier, 20 g of calcium oxide and 10 g of polyethylene glycol-200 and add them into a Haake internal mixer. The temperature of the internal mixer is set to 170° C. and the speed is 45 r / min for internal mixing for 20 min to obtain internal mixing plastic.
[0079] Add the mixed plastic into a two-roll mixer, set the temperature of the front roller to 175°C, the temperature of the rear roller to 165°C, adjust the distance between the two rollers to 5mm, pass through the mixer several times until it reaches the wrap roller, discharge the material, and obtain an injection molding precursor.
[0080] S3. Preparation of modified silicon dioxide
[0081] Weigh: 50 g of nano-silica, 400 mL of anhydrous ethanol, and 30 g of 3-aminopropyltriethoxysilane, add them into a three-necked flask, ultrasonically disperse for 50 min, transfer the three-necked flask to an iron stand with a mechanical stirrer, stir, add 150 mL of 8vt% ammonia water into the three-necked flask, raise the temperature of the three-necked flask to 60°C, keep warm for 5 hours, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake with purified water until it is neutral, transfer the filter cake to a drying oven at 70°C, and dry it to constant weight to obtain modified silica.
[0082] S4. Preparation of light absorbing modifier
[0083] Weigh: 15 g of 2,2-dihydroxymethylpropionic acid and 70 mL of cyclohexane are added to a three-necked flask and stirred. The temperature of the three-necked flask is raised to 55° C., 15 g of triethylamine is added dropwise to the three-necked flask. After the addition is complete, the reaction is kept warm for 50 minutes. The temperature of the three-necked flask is lowered to 20° C., and the mixture is kept warm and stirred for 15 minutes. The filter cake is filtered, and the filter cake is rinsed three times with cyclohexane and then dried. The filter cake is transferred to a drying oven at a temperature of 60° C. and dried to constant weight to obtain 2,2-dihydroxymethylpropionic acid salt;
[0084] Weigh: 30 g of 2,2-dihydroxymethylpropionate, 20 g of hydroxypropyl-terminated polydimethylsiloxane, 20 g of 1,5-pentanediol, 240 mL of xylene and 0.1 g of dibutyltin dilaurate, add them into a three-necked flask protected by nitrogen and stir, raise the temperature of the three-necked flask to the system micro-reflux, add 86 g of isophorone diisocyanate dropwise into the three-necked flask, after the addition is complete, keep warm and react for 120 min, weigh 140 g of modified silica, divide the modified silica into 5 equal parts, add them into the three-necked flask in batches, with an interval of 5 min between each batch, after the addition of modified silica is completed, keep warm and react for 3 h, raise the temperature of the three-necked flask to 100° C., evaporate toluene under reduced pressure, and post-treat to obtain a light absorbing modifier.
[0085] S5. Preparation of modified talcum powder
[0086] Weigh: 24.7 g of isocyanatepropyltriethoxysilane, 82.3 mL of tetrahydrofuran and 6.2 g of ethylene glycol, add into a three-necked flask protected by nitrogen, stir, react at room temperature for 3 h, and obtain a modified solution for standby use;
[0087] Weigh: 41.2 g of talcum powder, 164.8 mL of ethanol and 82.4 mL of 10 vt% ammonia water, add into a three-necked flask and ultrasonically disperse for 50 min, fix the three-necked flask on an iron stand with a mechanical stirrer and stir, raise the temperature of the three-necked flask to 60°C, add the modified liquid dropwise into the three-necked flask, keep warm for 5 h, lower the temperature of the three-necked flask to room temperature, filter, wash the filter cake three times with anhydrous ethanol and then drain, transfer the filter cake to a drying oven at 70°C, dry to constant weight, and obtain modified talcum powder.
[0088] S6, Automobile dashboard injection molding
[0089] Weigh: 1000g of injection molding precursor, 230g of light absorption modifier, 110g of modified talc, 20g of magnesium stearate, 20g of diisodecyl phthalate, 10g of tert-butylhydroquinone, and 10g of oleamide, and add them to a twin-screw extruder. The temperatures of the six temperature zones from the feed end to the discharge end of the twin-screw extruder are set to 250°C, 255°C, 260°C, 260°C, 260°C, and 260°C, respectively. The main shaft speed of the twin-screw extruder is 18r / min. The products are melt-extruded into a molding mold through the twin-screw extruder and demolded to obtain a car dashboard.
[0090] Comparative Example 1
[0091] The difference between this comparative example and Example 3 is that step S1 is omitted and no plastic modifier is added in step S2.
[0092] Comparative Example 2
[0093] The difference between this comparative example and Example 3 is that step S3 and step S4 are eliminated, and no light absorbing modifier is added in step S6.
[0094] Comparative Example 3
[0095] The difference between this comparative example and Example 3 is that step S5 is eliminated, and the modified talc in step S6 is replaced by an equal amount of talc in step S5.
[0096] Performance Test:
[0097] The gloss, wear resistance and mechanical strength of the automobile instrument panels prepared in Examples 1-3 and Comparative Examples 1-3 were tested, wherein the wear resistance was measured by referring to the standard GB / T 3960-2016 "Test Method for Sliding Friction and Wear of Plastics" to measure the mass wear of the sample, the gloss was measured by referring to the standard GB 8807-1988 "Test Method for Mirror Gloss of Plastics", and the mechanical strength was measured by referring to the standard GB / T 1843-2008 "Determination of Izod Impact Strength of Plastics" to measure the unnotched impact strength of the sample and the standard GB / T 1040.1-2018 "Determination of Tensile Properties of Plastics Part 1: General Principles" to measure the tensile strength and tensile fracture strain of the sample. The specific test results are shown in the following table:
[0098] Category Tensile strength / MPa Tensile strain at break / % Glossiness / % <![CDATA[Izod impact strength / kJ·m -2 > Mass wear / mg Example 1 35.6 197.3 15.5 39.5 23.5 Example 2 35.9 194.8 16.1 38.8 23.9 Example 3 35.3 198.6 15.2 39.2 23.6 Comparative Example 1 25.6 158.3 15.6 21.4 35.6 Comparative Example 2 25.8 164.2 29.4 22.3 27.7 Comparative Example 3 31.4 176.5 19.3 29.8 26.6
[0099] Data Analysis:
[0100] Comparing and analyzing the data in the above table, the tensile strength of the automobile instrument panel prepared by the present invention reaches 35.6MPa, the tensile fracture strain reaches 196.9%, the glossiness is reduced to 15.6%, and the unnotched impact strength reaches 39.2kJ / m -2 , the mass wear is reduced to 23.7mg, and all test data are better than those of the comparative example, indicating that the present invention modifies PVC powder and nitrile rubber by a plastic modifier, prepares an injection molding precursor and then cooperates with modified talcum powder and the prepared light-absorbing modifier to prepare a car dashboard with good tensile properties, stable impact resistance, low gloss and wear resistance.
[0101] The above contents are merely examples and explanations of the structure of the present invention. The technicians in this technical field may make various modifications or additions to the specific embodiments described or replace them in a similar manner. As long as they do not deviate from the structure of the invention or exceed the scope defined by the claims, they should all fall within the protection scope of the present invention.
[0102] In the description of this specification, the description with reference to the terms "one embodiment", "example", "specific example", etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms does not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described can be combined in any one or more embodiments or examples in a suitable manner.
[0103] The preferred embodiments of the present invention disclosed above are only used to help explain the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to only specific implementation methods. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. A method for injection molding a low-gloss, wear-resistant automobile instrument panel, characterized in that: The following steps are involved: S1. Add 4-hydroxyphenylboric acid and tetrahydrofuran into a three-necked flask and stir until the system is dissolved, add 3-mercapto-1,2-propanediol and a catalyst into the three-necked flask, raise the temperature of the three-necked flask to 45-55° C., keep the temperature for reaction for 8-10 hours, and perform post-treatment to obtain a plastic modifier; S2, adding PVC powder, nitrile rubber, plastic modifier and additives into a Haake internal mixer, and mixing for 15-20 minutes to obtain internally mixed plastic, wherein the additives are composed of calcium oxide and polyethylene glycol-200 in a weight ratio of 2:1; Add the mixed plastic into a two-roll mixer, set the temperature of the front roller to 165-175°C, the temperature of the rear roller to 160-165°C, adjust the distance between the two rollers to 3-5mm, pass through the mixer several times until the rollers are wrapped, and discharge the material to obtain an injection molding precursor; S3, adding 2,2-dihydroxymethyl propionate, hydroxypropyl-terminated polydimethylsiloxane, 1,5-pentanediol, xylene and a catalyst into a three-necked flask protected by nitrogen and stirring, raising the temperature of the three-necked flask to a micro-reflux of the system, adding isophorone diisocyanate dropwise into the three-necked flask, and after the addition is complete, heat-retaining the reaction for 90-120 minutes, adding modified silica into the three-necked flask in multiple batches, and after the addition of the modified silica is complete, heat-retaining the reaction for 2-3 hours, and post-treating to obtain a light-absorbing modifier; S4, adding an injection molding precursor, a light absorbing modifier, modified talcum powder and additives into a twin-screw extruder, melt-extruded into a molding die, and demolded to obtain an automobile instrument panel, wherein the weight ratio of the injection molding precursor, the light absorbing modifier, the modified talcum powder and the additive is 100:23:11:6, and the additive is composed of a dispersant, a plasticizer, an antioxidant, and a lubricant in a weight ratio of 2:2:1:1; The preparation method of modified silicon dioxide is as follows: adding nano silicon dioxide, anhydrous ethanol and 3-aminopropyltriethoxysilane into a three-necked flask, ultrasonically dispersing for 30-50 minutes, transferring the three-necked flask to an iron stand with a mechanical stirrer, stirring, adding 8vt% ammonia water into the three-necked flask, raising the temperature of the three-necked flask to 50-60°C, keeping the temperature for reaction for 4-5 hours, and post-treating to obtain modified silicon dioxide; The preparation method of modified talcum powder is: Add isocyanatepropyltriethoxysilane, tetrahydrofuran and ethylene glycol into a three-necked flask protected by nitrogen, stir, and react at room temperature for 2-3 hours to obtain a modified solution for later use; Add talcum powder, ethanol and 10vt% ammonia water into a three-necked flask and ultrasonically disperse for 30-50min. Fix the three-necked flask on an iron stand with mechanical stirring and stir. Raise the temperature of the three-necked flask to 50-60℃. Add the modified liquid dropwise into the three-necked flask. After the addition is complete, keep the temperature for reaction for 3-5h and post-treat to obtain modified talcum powder.
2. The method for injection molding a low-gloss, wear-resistant automobile instrument panel according to claim 1, characterized in that: In step S1, the molar ratio of 4-hydroxyphenylboric acid and 3-mercapto-1,2-propylene glycol is 1:1, the 4-hydroxyphenylboric acid, tetrahydrofuran and catalyst are 1 g:5 mL:0.1 g, and the catalyst is deionized water; in step S2, the weight ratio of PVC powder, nitrile rubber, plastic modifier and additive is 70:30:4:3, the temperature of the internal mixer is 160-170°C, and the rotation speed is 35-45 r / min.
3. The method for injection molding a low-gloss, wear-resistant automobile instrument panel according to claim 1, characterized in that: The preparation method of 2,2-dihydroxymethyl propionate is as follows: 2,2-dihydroxymethyl propionic acid and cyclohexane are added into a three-necked flask and stirred, the temperature of the three-necked flask is increased to 50-55° C., triethylamine is added dropwise into the three-necked flask, and after the addition is completed, the reaction is carried out by heat preservation for 30-50 minutes, and 2,2-dihydroxymethyl propionate is obtained by post-treatment.
4. The method for injection molding a low-gloss, wear-resistant automobile instrument panel according to claim 3, characterized in that: The dosage ratio of the 2,2-dihydroxymethylpropionic acid, cyclohexane and triethylamine is 1g:6mL:1g, and the post-treatment operation includes: after the reaction is completed, the temperature of the three-necked flask is reduced to 10-20°C, the mixture is stirred for 10-15min, filtered, the filter cake is rinsed three times with cyclohexane and then dried, the filter cake is transferred to a drying oven at a temperature of 50-60°C, and dried to constant weight to obtain 2,2-dihydroxymethylpropionic acid salt.
5. The method for injection molding a low-gloss, wear-resistant automobile instrument panel according to claim 1, characterized in that: The dosage ratio of the nano silicon dioxide, anhydrous ethanol, 3-aminopropyltriethoxysilane and 8vt% ammonia water is 5g:40mL:3g:15mL.
6. The method for injection molding a low-gloss, wear-resistant automobile instrument panel according to claim 1, characterized in that: The molar ratio of the isocyanatepropyl triethoxysilane and ethylene glycol is 1:1, and the dosage ratio of the isocyanatepropyl triethoxysilane, tetrahydrofuran, talcum powder, ethanol and 10vt% ammonia water is 3g:10mL:5g:20mL:10mL.
7. The method for injection molding a low-gloss, wear-resistant automobile instrument panel according to claim 1, characterized in that: In step S3, the dosage ratio of 2,2-dihydroxymethylpropionate, hydroxypropyl-terminated polydimethylsiloxane, 1,5-pentanediol, xylene, catalyst, isophorone diisocyanate and modified silica is 1.5g:1g:1g:12mL:0.05g:4.3g:7g, and the catalyst is dibutyltin dilaurate.
8. The method for injection molding a low-gloss, wear-resistant automobile instrument panel according to claim 1, characterized in that: In step S4, the dispersant is one or more of calcium stearate, zinc stearate, magnesium stearate, and cadmium stearate, the plasticizer is one or more of dioctyl phthalate, diester phthalate, diisodecyl phthalate, and tricresyl phosphate, the antioxidant is one or more of butylated hydroxyanisole, dibutyl hydroxytoluene, and tert-butylhydroquinone, and the lubricant is one or more of oleamide and ethylene bisstearamide; the temperatures of the six temperature intervals of the twin-screw extruder from the feed end to the discharge end are set to 250°C, 255°C, 260°C, 260°C, 260°C, and 260°C, respectively, and the spindle speed of the twin-screw extruder is 18r / min.
Citation Information
Patent Citations
Polyamide resin with high wear resistance, and preparation method thereof
CN108219446A
High-temperature-resistant composite cable for electric automobile
CN116936170A